Linking ‘Halal’ friendly hotel attributes and customer satisfaction : the islamic tourism sector / Lennora Putit ... [et al.] - Putit, Lennora; Muda, Mazzini; Mahmood, Ainul Nadzirah; Ahmad Taufek, Nor Zafirah; Wahib, Norhayati (Universiti Teknologi Mara Selangor, 2016)
An increasing demand for Islamic tourism has driven the concept of a ‘Halal’ (or permissible) friendly hotel into another level of business insight within the consumers’ travel market. The concept via its unique value proposition has rapidly become very attractive not only to Muslim tourists, but also to non-Muslim tourists globally. This study aims to examine the relationship linking ‘Halal’ friendly hotel attributes and customer satisfaction. Using purposive sampling, a total of 410 survey questionnaires were distributed to targeted respondents with only 323 usable feedbacks and used for data analysis. Regression results revealed that four main “Halal-friendly hotel” attributes have significant relationships with customer satisfaction. These include prayer facilities, Halal food, Islamic dress code and general Islamic morality. Of these four attributes, prayer facilities proved to have the most significant impact on customer satisfaction. Findings and managerial implications were further discussed in this article.